Tintinalli's Emergency Medicine Manual - Cydulka, Rita K.; Fitch, Michael T.; Joing, Scott A.; Wang, Vincent J.; Cline, David M.; Ma, O. John (McGraw-Hill Education, 2018)
Covering the full spectrum of emergency medicine in all patient populations - adult and pediatric - this full-colour guide is composed of concise chapters that focus on clinical features, diagnosis and differential, and emergency management and disposition. This new edition includes extensive updates to all sections, incorporating the latest guidelines, evidence-based protocols, and relevant research.